Correction: Soft modes and strain redistribution in continuous models of amorphous plasticity: the Eshelby paradigm, and beyond?. Issue 18 (27th April 2018) - Cao, Xiangyu; Nicolas, Alexandre; Trimcev, Denny; Rosso, Alberto
Abstract : Correction for 'Soft modes and strain redistribution in continuous models of amorphous plasticity: the Eshelby paradigm, and beyond?' by Xiangyu Cao et al., Soft Matter, 2018, DOI: ;10.1039/c7sm02510f .